2003
DOI: 10.1046/j.1445-2197.2003.02818.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Tongue Cancer: Age Is Not a Predictor of Outcome and Should Not Alter Treatment

Abstract: In keeping with recently published evidence, young age at diagnosis with anterior tongue cancer did not portend worse outcome. There is therefore currently no strong evidence to support a different treatment approach in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
43
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
5
43
2
4
Order By: Relevance
“…Age and gender did not influence the OS and DFS, similar to the observed in several studies (25-27). Tobacco and alcohol consumption also did not influence the outcome of these patients, as observed by Vallecillo-Capilla et al (13).…”
Section: Discussionsupporting
confidence: 90%
“…Age and gender did not influence the OS and DFS, similar to the observed in several studies (25-27). Tobacco and alcohol consumption also did not influence the outcome of these patients, as observed by Vallecillo-Capilla et al (13).…”
Section: Discussionsupporting
confidence: 90%
“…Veness et al (18) reported that the proportion of poorly-differentiated tumors in the young group was greater, however, Manuel et al (9) and Atula et al (15) reported that the majority of the tumors in their series were well-differentiated. In the present study, tumor differentiation was identified to be the most important prognostic factor for young patients and was found to significantly correlate with the RFS (P=0.016) and DSS (P=0.041) rates.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the studies conducted to date on the potential prognostic significance of age in tongue cancer have yielded conflicting results 4–17 . This might be explained by the almost exclusive use of 40–45 years as the cut‐off for comparison, with a wide range of mean ages, from 30 to 38 years.…”
mentioning
confidence: 99%